Stopnja fikcionalizacije v Dnevniku Andreja Čeboklija - Bandelj, David (Primerjalna književnost, 2005)
The level of fictionalisation in Andrej Čebokli's Dnevnik. The paper initially deals with a definition of literary diaries as a subject of research in literary studies. Based on sources from literary sciences and studies conducted by theoreticians in Slovenia and Europe, the article attempts to establish the grounds for theories on diary writings and to determine research perspectives. The second part of the study focuses on Dnevnik (Diary) by Andrej Čebokli, applying the relevant theory especially to the author's fictionalisation of actual events and activities.
Keywords: Čebokli, Andrej, 1893-1923; dnevniki; literarna teorija; literary theory; Čebokli, Andrej: Andrej Čebokli; literarne študije; fikcionalnost; Slovene literature; slovenska književnost